CRF and urocortin peptides as modulators of energy balance and feeding behavior during stress - Stengel, Andreas; Taché, Yvette F. (Frontiers in Neuroscience, 2014)
Early on, corticotropin-releasing factor (CRF), a hallmark brain peptide mediating many components of the stress response, was shown to affect food intake inducing a robust anorexigenic response when injected into the rodent brain. Subsequently, other members of the CRF signaling family have been identified, namely urocortin (Ucn) 1, Ucn 2, and Ucn 3 which were also shown to decrease food intake upon central or peripheral injection. However, the kinetics of feeding suppression was different with an early decrease following intracerebroventricular injection of CRF and a delayed action of Ucns contrasting with the early onset after systemic injection. CRF and Ucns bind to two distinct G-protein coupled membrane receptors, the CRF1 and CRF2. New pharmacological tools such as highly selective peptide CRF1 or CRF2 agonists or antagonists along with genetic knock-in or knock-out models have allowed delineating the primary role of CRF2 involved in the anorexic response to exogenous administration of CRF and Ucns. Several stressors trigger behavioral changes including suppression of feeding behavior which are mediated by brain CRF receptor activation. The present review will highlight the state-of-knowledge on the effects and mechanisms of action of CRF/Ucns-CRF1/2 signaling under basal conditions and the role in the alterations of food intake in response to stress.